Is professional exam performance associated with career success for Big 4 auditors? Evidence on gender differences - Fredriksson, Antti; Hay, David; Karjalainen, Jukka; Maghakyan, Arpine; Niemi, Lasse (Contemporary Accounting Research, 2025)
Abstract This study examines whether better performance on the Certified Public Accountant (CPA) exam is associated with an auditor's career success and whether any relation differs based on gender. Our study adds to prior studies on the career development of auditors by showing that the auditor's performance on the exam predicts success during the auditor's career. Although there is little difference in the average CPA exam scores of male versus female auditors, we document gender differences in the relation between performance on the CPA exam and career success. Male auditors who pass the exam with superior results receive higher annual compensation than those with weaker results. They are also more likely to become partners in Big 4 accounting firms and have larger client portfolios. For female auditors, we find weaker or no association between CPA exam scores and compensation or other indicators of career success. Our path analysis shows that the mechanisms underlying career success work differently for men and women. CPA exam scores of male auditors have a direct effect on compensation and an indirect (mediating) effect through promotion to partner and client portfolio size. However, for female auditors, exam scores have no effect on promotion to partner or client portfolio size, and exam scores have a much smaller effect on compensation. Our findings suggest that CPA exam scores translate into career success for male auditors but not for female auditors.